Characterization of tinopal CBS-X as a fluorescent tracer in cooling water. Issue 3 (4th May 2017) - Wang, Jiajia; Peng, Yuting; Guo, Wenya; Ji, Ruijuan; Zhao, Liang; Jia, Yuzhu; Gao, Canzhu
ABSTRACT: This article reports the use of Tinopal CBS-X as a fluorescent tracer in circulating cooling water. The fluorescence of CBS-X was characterized at various conditions; the intensity was not affected by high concentrations of ionic compounds and organophosphorus compounds, temperature changes, and variations in pH. The concentrations of CBS-X and scale inhibitors were employed to eliminate the influence of biocides. In summary, fluorescent tracing with Tinopal CBS-X was simple and rapid with a low detection limit and may provide application for the determination of other treatment agents.